THE INTERNATIONAL CRIMINAL COURT IN GUINEA: A CASE STUDY OF COMPLEMENTARITY - Colish, Will (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional)

(untitled) (Société québécoise de droit international, 2013)
The International Criminal Court (ICC) and domestic criminal justice systems work together to prosecute the worst crimes through the principle of complementarity. This principle, enshrined in article 17 of the Rome Statute, holds that the Court will only intervene if a State is either unwilling or unable to investigate crimes falling within the Court’s jurisdiction. Since the entry into force of the Rome Statute, complementarity has evolved with practice. The Office of the Prosecutor now adopts a practice of “positive complementarity”, meaning that, more than simply wait on the sidelines to determine whether a State is both willing and able, the Court now takes an active role in helping a State fulfil its Rome Statute obligations. Positive complementarity treats as permeable the border between the ICC and States, through which expertise, coordination, and documentation pass in an effort to end impunity. But there are various ways in which the Court and States can work together in this process. The current practice leans on international networks and actors to help a State investigate and prosecute. While the addition of these actors can channel resources toward the aim of justice, competing aims of the players within these networks can make for a confused picture at best; at worst they can tear open large impunity gaps that no prosecutorial strategy could tolerate. The case of Guinea forebodes these gaps and provides important lessons on how they may be closed through a more proactive approach to complementarity—such is the focus of this article.